Effectiveness and safety of secukinumab in 69 patients with moderate to severe plaque psoriasis: A retrospective multicenter study. Issue 6 (14th September 2017) - Schwensen, J. F.; Clemmensen, A.; Sand, C.; Gniadecki, R.; Skov, L.; Zachariae, C.; Iversen, L.; Rasmussen, M.; Thomsen, S. F.
Abstract: Secukinumab (anti‐IL17A) is effective as treatment for moderate to severe plaque psoriasis, but real‐life data on effectiveness and safety lack. We aimed to present real‐life data of all Danish patients treated with secukinumab ( n  = 69). At baseline, before initiation of treatment with secukinumab 300 mg (47.8%) or off‐label treatment with secukinumab 150 mg (52.2%), the median PASI score was 7.1. A total of 66.7% (34/51) and 52.9% (27/51) of patients still on secukinumab at week 12 achieved a PASI (Psoriasis Area and Severity Index)‐50 and PASI‐75 of 66.7% and 52.9%, respectively. A total of 83.0% (44/53) and 60.4% (32/53) of the patients had a PASI‐score < 5 and PASI‐score < 2, respectively, after 12 weeks on treatment with secukinumab. A third of the patients had secukinumab discontinued due to limited clinical improvement or adverse events ( n  = 23) within a median of 92 days (interquartile range 51–212 days). Notably, the majority of the patients may represent a particularly difficult‐to‐treat group of patients, as 92.8% had been refractory to other biologic treatment. A total of 26.1% ( n  = 18) experienced adverse events. Secukinumab appears to be an effective treatment option with a favorable side effect profile in patients with plaque psoriasis who are refractory to or have side effects of traditional biologic drugs.